Guest Editors’ Introduction: What is Psychoanalysis Today? A Critique of Psychoanalytic Theory and Clinic from the Philosophical Point of View - Barria-Asenjo, Nicol A.; Žižek, Slavoj (Revista de Humanidades de Valparaíso, 2023)
In this paper, we seek to draw new lines of demarcation in relation to the debates concerning both Philosophy and Psychoanalysis. Through the historical trajectory of the psychoanalytic movement, the reader is shown the importance of disciplinary mixtures. Namely, interdisciplinary dialogues that psychoanalysis in its theory and practice maintained since early times. It is proposed to think Psychoanalysis and Philosophy as a knot that finds its usefulness and responsibility in the social and political field. That is to say, the mixture and the collision between the conceptual machineries of both fields of knowledge contribute to think and analyze the situation of our century.